Education-based grant programmes for bottom-up distance learning and project catalysis: Antimicrobial Resistance in Sub-Saharan Africa - Graham, Christopher, Laurie, Barnett; Akligoh, Harry; King’Ori, Joy; Adzaho, Gameli; Salekwa, Linda; Campbell, Patrick; Saba, Courage; Landrain, Thomas; Santolini, Marc (My University, 2022)
International development and aid are often conducted through the allocation of funding determined by decisions of non-locals, especially in the west for those in the global south. In addition, such funding is often disassociated from local expertise, therefore providing little long-term developmental impact and generating distrust. This is particularly true for conservation, as well as environmental and educational programmes. We hypothesise that by granting local people the educational tools and the necessary funding to develop their own projects through the use of an applicant driven peer-review approach, it is possible to relocalize the decision-making process to the programme participants, with the potential to generate and select more relevant projects with developmental outcomes of higher quality. Here we created an online curriculum for antimicrobial resistance (AMR) education that was followed by 89 participants across Ghana, Tanzania, Nigeria, and Uganda. We then created an open research programme that facilitated the creation of eight de novo projects on AMR. Finally, we organised an applicant-driven grant round to allocate funding to the “Neonatal Sepsis in Nigeria” project to conduct a pilot study and awareness campaign. This work opens perspectives for the design of frugal educational programmes and the funding of context-specific, community-driven projects aimed at empowering local stakeholders in the global South.
Keywords: Community Review; Grant allocation; AMR; Online Curriculum; Web platform; Decision making